El principio de presunción de inocencia y la prisión preventiva cómo medida excepcional, en la provincia de Imbabura. - Játiva, Marcelo J. (2022)
The present investigation is determined in order to analyze the principle of innocence and the applicability of article 534 established in the reform of the Organic Comprehensive Criminal Code regarding the suspension of preventive detention; being able to identify several shortcomings in said application, among which there is the lack of minimum requirements for criminal law transgressors to be beneficiaries, as well as the lack of legal and personal security of the victims, violating the principle of legal security enshrined in the Constitution, although it is true that preventive detention is the last resort as determined by our Magna Carta, we cannot end up favoring some and leaving aside the rights of the victims, since with this reform we can realize that the balance between victim and defendant, the protection of their rights and procedural equality, with the sole purpose of avoiding disparity when making the correct decisions by justice administrators. For this scientific article, legal analysis and its application at the level of the province of Imbabura were used. The approach used for this research work is qualitative-quantitative. Starting as a result of the investigation the need to structure a proposal to reform article 534 of the Organic Comprehensive Criminal Code regarding the minimum requirements that should be met to benefit from the suspension of preventive detention.